PENDEKATAN BEHAVIORAL (TEKNIK REINFORCEMENT) UNTUK MENINGKATKAN PERILAKU PROSOSIAL ANAK USIA 5-6 TAHUN DI TK AISYIYAH III KOTA PEKANBARU - Wahyuni, Sri; Efastri, Sean Marta (Universitas Hamzanwadi, 2019)
Through a behavioral approach the child will interact with peers, interaction with peers is needed by children so that all activities in school can run as desired. Prosocial in children must be fostered early on. The research conducted was Classroom Action Research, data analysis using quantitative data analysis techniques with research subjects children aged 5-6 years at TK Aisyiyah III Pekanbaru City. the results of this study can be concluded that the prosocial behavior of B3 TK Aisyiyah III group can be improved through a behavioral approach ( reinforcement techniques). Increased child prosocial behavior can be seen in the results of pre-action research obtained 45% are in undeveloped criteria. In the first cycle meeting 2 was obtained 59% which is in the criteria began to develop. In the second cycle meeting 2 obtained 76% of children are in the criteria of developing according to expectations. The study was stopped until the second cycle because it met the criteria for success indicators that is at least 70% of children whose prosocial behavior developed as expected.